Penggunaan Alat Peraga TAPASAM Sebagai Upaya Meningkatkan Kemampuan Berhitung Bagi Anak - Khotim Fadhli; Ita Rahmawati; Muhammad Farid Nasrulloh; Febri Devita Lisgita Putri; Martina Martina; Mohammad Ali Rosyid (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2022)
The community service carried out aims to improve numeracy skills for early childhood in Rejosopinggir village. Service activities in Rejosopinggir Village, Tembelang District, Jombang Regency, East Java. The implementation of community service activities will be carried out in December 2021. The implementation method for implementing this community service activity includes the Participatory Action Research method. Action and participatory methods are carried out in mentoring parents and children about increasing children's abilities in certain fields. The community service activities carried out concluded that the use of TAPASAM teaching aids (paired and connected ropes) could improve numeracy skills for early childhood. The existence of assistance to children in Rejosopinggir village by introducing learning media in the form of TAPASAM props (paired and connected ropes) can improve numeracy skills for early childhood in Rejosopinggir village. The choice of learning media will be very influential in exploring children's achievements so that the TAPASAM media (paired and continuous ropes) is interesting in activating children's learning creativity. Keywords : media / props, numeracy skills, children's education